2012
DOI: 10.1016/j.echo.2012.05.004
|View full text |Cite
|
Sign up to set email alerts
|

The Ventricular Volume Variability Study of the Pediatric Heart Network: Study Design and Impact of Beat Averaging and Variable Type on the Reproducibility of Echocardiographic Measurements in Children with Chronic Dilated Cardiomyopathy

Abstract: Clinical trials often rely on echocardiographic measures of left ventricular (LV) size and function as surrogate end-points. However, the quantitative impact of factors that affect reproducibility of these measures is unknown. To address this issue, the NHLBI-funded Pediatric Heart Network designed a longitudinal observational study of children with known or suspected dilated cardiomyopathy (DCM) aged 0–22 years from 8 pediatric clinical centers. Methods Clinical data were collected together with 150 echocard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
70
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 22 publications
11
70
0
1
Order By: Relevance
“…Commonly used methods have included the Pearson correlation coefficient, percentage error, intraclass correlation coefficient, and k statistic. [21][22][23] The limitations of these statistical methods are that they are influenced by population characteristics, lack data on individual readers, and are dependent on the range of data in the analyzed sample. 18,19,24 For example, the intraclass correlation coefficient for the initial evaluation of LVEDV in this study was 0.88, which is seemingly a good correlation for the group but does not provide any information about individual variability such as that seen with reader A, nor does it indicate the source of interpretative error.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Commonly used methods have included the Pearson correlation coefficient, percentage error, intraclass correlation coefficient, and k statistic. [21][22][23] The limitations of these statistical methods are that they are influenced by population characteristics, lack data on individual readers, and are dependent on the range of data in the analyzed sample. 18,19,24 For example, the intraclass correlation coefficient for the initial evaluation of LVEDV in this study was 0.88, which is seemingly a good correlation for the group but does not provide any information about individual variability such as that seen with reader A, nor does it indicate the source of interpretative error.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies on reproducibility have provided valuable insight about the inconsistency of echocardiographic results in research and clinical practice, but these studies were generally descriptive evaluations of reproducibility that lacked recommendations or effective interventions to minimize variability once it was identified. 11,21 These studies limited the evaluation of interobserver variability and echocardiographic reproducibility to a few parameters (most commonly LV function) or a single disease entity. [11][12][13]16,21 In contrast, we included eight clinically important echocardiographic parameters, as well as a spectrum of cardiac pathologies commonly encountered in clinical practice to make certain that this method was broadly applicable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Care was taken to keep the ultrasound beam aligned parallel to the VS and RV free wall. Images were graded according to the scoring system [20], and only images graded as excellent or good were included in the following analysis. Regions of interest were manually positioned on the right and left sides of the VS separated by a bright line and the RV free wall, both at the middle part of the wall (Figs.…”
Section: D Speckle-tracking Echocardiographymentioning
confidence: 99%
“…Many reports have been published comparing echo diagnoses with data from other modalities (such as cardiac magnetic resonance imaging, computed tomography imaging, and cardiac catheterization) as well as fi ndings in the operating room during surgery [ 19 -22 ]. More recently, other publications have evaluated multi-acquisition, intra-observer, and inter-observer variability for echo measurements and have shown that some measurements are more prone to poor repeatability than others, even with multiple heart beat averaging [ 23 ]. The IAC has developed specifi c recommendations for quarterly correlation assessments (to compare echo fi ndings in specifi c instances with results from other modalities and from the operating room) and variability assessments (to evaluate the repeatability of specifi c measurements performed during an echo) [ 18 ].…”
Section: Study Interpretationmentioning
confidence: 98%